Kontribusi Aplikasi Nilai Kepramukaan bagi Pembinaan Kepribadian Siswa Sekolah Dasar - A Hardoko (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2007)
Abstract: Pramuka (Boy Scout) activities can build full personality. The pramuka activities that are educational games based have objective to develop personality, social needs, state building, and nation building. The activities should be based on among system”Ing ngarso sung tulodo, ing madyo mangun karso, tut wuri handayani”. The value of Pramuka can help elementary school students become good citizens, active loyalty, creative, and innovative through training of character, cleanness and power, handy craft and skills, and pro-social behavior (task-force system).